A test of the theory of nonrenewable resources: Controlling for exploration and market power - Raimund Malischek; Christian Tode (Institute of Energy Economics at the University of Cologne (EWI), 2015)
Despite the central role of the Hotelling model within the theory of nonrenewable resources, tests of the model are rarely found. If existent, these tests tend to ignore two key features, namely market power and exploration. We therefore suggest an extension of the basic Hotelling framework to incorporate exploration activity and market power and propose an implicit price behavior test of the model to indicate whether firms undergo inter-temporal optimization. When applied to a newly constructed data set for the uranium mining industry, the null hypothesis of the firm optimizing inter-temporally is rejected in all settings. However, parameter estimates of the model still yield valuable information on cost structure, resource scarcity and market power. Our results suggest that the shadow price of the resource in situ is comparably small and may be overshadowed by market power, which may serve as an explanation for the firm failing to optimize inter-temporally.
Keywords: D92; L13; L72; Q31; 330; Hotelling rule; Resource Economics; Resource Scarcity; Dynamic Optimization; Exploration; Market Power; Hausman Test